2018
DOI: 10.1080/10255842.2018.1490954
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic energy expenditure model with a continuous first derivative and its application to predictive simulations of gait

Abstract: Whether humans minimize metabolic energy in gait is unknown. Gradient-based optimization could be used to predict gait without using walking data but requires a twice differentiable metabolic energy model. Therefore, the metabolic energy model of Umberger et al. ( 2003 ) was adapted to be twice differentiable. Predictive simulations of a reaching task and gait were solved using this continuous model and by minimizing effort. The reaching task simulation showed that energy minimization predicts unrealistic move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 27 publications
0
70
0
Order By: Relevance
“…This gait pattern requires smaller knee extension torques. Biomechanics researchers have suggested that gait with near-zero joint torques is unstable and that taking uncertainty into account would lead to more optimal movements with larger knee flexion during stance and larger knee extension torques as consequence [Koelewijn et al 2018]. Figure 7 visualizes the learned torque limits for different states.…”
Section: Runningmentioning
confidence: 99%
“…This gait pattern requires smaller knee extension torques. Biomechanics researchers have suggested that gait with near-zero joint torques is unstable and that taking uncertainty into account would lead to more optimal movements with larger knee flexion during stance and larger knee extension torques as consequence [Koelewijn et al 2018]. Figure 7 visualizes the learned torque limits for different states.…”
Section: Runningmentioning
confidence: 99%
“…As an illustration, we added a term representing the metabolic energy rate [30] to the objective function of the 2D predictive simulations. Minimizing metabolic energy rate is common in predictive studies of walking [4,6,24]. Solving the resulting optimal control problem was about 60 times faster with AD-Recorder than with FD (although FD required fewer iterations), whereas AD-Recorder was only about 10 times faster than FD without incorporating the metabolic energy rate in the objective function.…”
Section: Discussionmentioning
confidence: 99%
“…Solving the resulting optimal control problem was about 60 times faster with AD-Recorder than with FD (although FD required fewer iterations), whereas AD-Recorder was only about 10 times faster than FD without incorporating the metabolic energy rate in the objective function. This increased time difference can be explained by our use of computationally expensive hyperbolic tangent functions to make the metabolic energy rate model twice continuously differentiable, as required when using second-order gradient-based optimization algorithms [24]. Overall, AD reduces the number of function evaluations, which has an even larger effect if these functions are expensive to compute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of direct collocation have led biomechanists to use the method for tracking motions [16,23], predicting motions [24][25][26][27][28][29][30][31][32][33], fitting muscle properties [34], and optimizing design parameters [35]. Researchers have made key methodological advances, including efficiently handling multibody and muscle dynamics via implicit formulations [36,37], minimizing energy consumption [38,39], and employing algorithmic differentiation to simulate complex models more rapidly compared to using finite differences [40]. Along with these methodological advances, researchers have discovered that minimizing an energy-related cost produces non-physiological motions during walking [24], skipping is the most efficient gait on our moon [41], and unilateral amputees can improve gait symmetry with only a minor increase in effort [42].…”
Section: Introductionmentioning
confidence: 99%